Social media as a promotional strategy for Sredekan art in Karangsari village - Shubuha Pilar Naredia (Universitas Islam Sultan Agung, 2026)
The construction of Jlantah Dam exerts substantial impact, the lost of land most of which belongs to Karangsari villagers. The Karangsari villagers’ lost land then changes into new settlement region as the manifestation of compensation. The new settlement region is called billionaire village. There is a local art, called Sredekan, also changing in the village. This study aims to describe an innovation- and creation-based promotion strategy in Sredekan art to support sustainable development in Karangsari billionaire village, Jatiyoso with Talcott Parsons’ structural functional scheme. This study is a type of qualitative research that focuses on a single case to explore it thoroughly. The data was gathered using observation, detailed interviews, and review of documents. Supported data derived from literature linear to the focus of research. Informants were selected using snowball sampling. The instruments used were interview guidelines, field notes, and documentation. Data analysis was conducted in stages using the AGIL technique, and data credibility was tested using source triangulation.Based on research data located in the billionaire village of Karangsari, Jatiyoso, it can be seen that the innovation- and creation-based promotion strategy in Sredekan art to support sustainable development in Karangsari billionaire village, Jatiyoso includes more flexible stage location, denser staging duration, modernization in staging attribute, and content production. Specifically within the newly formed settlement known as the 'Billionaire Village.' This strategy, developed to support sustainable development, included more flexible stage locations expanding from traditional sites near the Jlantah River to various external venues denser staging durations, modernization in staging attributes, and digital content production The change is defined as the existence of Sredekan art maintained the people as an integrated system working through AGIL (adaption, goal-attainment, integration, latency) scheme. Based on the research findings concerning the transformation of Sredekan art in Karangsari Village, the researchers may consider exploring how the integration of digital promotion strategies and modernization of staging attributes can be further optimized to balance the preservation of sacred cultural values with the demands of global cultural tourism.